Избранные методы воспитания Антона Макаренко в педагоги- ческой деятельности Марины Аромтшам - Jeleńska, Weronika (Acta Polono-Ruthenica, 2021)
This article is devoted to the main principles of the Russian pedagogical system of Anton Makarenko (1888–1939) and their implementation in Russian pedagogy a few decades later. The research is based on the theory and methods of education presented in Makarenko’s The Pedagogical Poem and Lectures on the Education of Children, which were compared with the methods of education in modern Russian schools, using the example of the pedagogical activity of Marina Aromshtam (born 1960), described in the work As a Diary. Stories of the Teacher. The basic principles that Makarenko introduced into his system of collective education are often used by modern teachers. In his work with children, he was guided primarily by their well-being and attached great importance to the individual development of the individual as well as education with the participation of parents. A comparative analysis has shown that Makarenko’s rejected and criticized methods are still present in the creation of the latest pedagogical systems, since the innovative pedagogical method of education of Marina Aromshtam, which has been developed since the 90s, is closely connected with the pedagogical legacy of Makarenko.